Majas Dalam Antologi Puisi Aksara Rasa Karya Aulia Irmawati Dkk Dan Implikasinya Dalam Pembelajaran Sastra Di SMP - Sandi Fitriono; Tri Mulyono; Khusnul Khotimah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
The purpose of this research; describes the figure of speech used in the poetry anthology of Aksara Rasa by Aulia Irmawati et al and describes the implementation of the results of the figure of speech research in teaching literature in junior high schools. This study used a descriptive analytical research method with the data source in this study being the poetry anthology of Aksara Rasa by Aulia Irmawati et al. The form of data is in the form of words, phrases and sentences that contain figures of speech in poetry quotes. The data analysis technique uses observing and note-taking techniques. Data analysis technique uses semantic analysis. The results of the study proved that the figurative language contained in the poetry anthology of Aksara Rasa by Aulia Irmawati et al. analyzed as many as 131 data. The data is divided into 4 classifications, namely 50 data for comparison, 30 for conflict, 27 for linking, and 24 for repetition. This maja research is implemented into teaching literature in junior high school on basic competencies 3.7 and 3.8 in the grade 8 Indonesian syllabus which identify elements of poetry and present ideas by paying attention to elements of poetry